2017
DOI: 10.5539/ies.v10n2p139
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cooperative Round Robin Discussion Model to Improve Students’ Holistic Ability in TEFL Class

Abstract: This classroom action research is carried out within two cycles to breed a strategy on how a Round Robin Discussion Learning Model enhance students' critical thinking, presentation skills, confidence, and independent learning in Teaching English as a Foreign Language (TEFL) class. Pop-up quiz, teacher made-tests, classroom participation sheet, observation sheet, and rubric are utilized in the study. In addition, the collected data are then scrutinized via quantitative and qualitative doctrine. Quantitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In order to stimulate conversation inside the classroom, students' PowerPoint presentations along with the animated films that accompany them are exhibited utilizing infocus and the internet. According to Asari et al (2018) the teacher acted as a moderator for a discussion in which the students utilized PowerPoint slides that they had prepared to provide their own explanations of the topics discussed in the class. Participants engage in group discussions on the aforementioned issues in order to provide them the opportunity to independently investigate their own knowledge and find validity in the aforementioned thoughts.…”
Section: Pedagogic Technology Capabilitymentioning
confidence: 99%
“…In order to stimulate conversation inside the classroom, students' PowerPoint presentations along with the animated films that accompany them are exhibited utilizing infocus and the internet. According to Asari et al (2018) the teacher acted as a moderator for a discussion in which the students utilized PowerPoint slides that they had prepared to provide their own explanations of the topics discussed in the class. Participants engage in group discussions on the aforementioned issues in order to provide them the opportunity to independently investigate their own knowledge and find validity in the aforementioned thoughts.…”
Section: Pedagogic Technology Capabilitymentioning
confidence: 99%
“…In this study, the concept of Round Robin technique (R2P) allowed students to speak accurately and fluently like native speakers, to speak fluently and accurately they must have enough vocabularies, expressions and be able to share opinions. Round Robin technique was used because this kind of technique has been done by previous researchers Desnita et al (2022) and Asari et al (2018) both studies revealed that Round Robin technique was effective to improve students' speaking skill.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the new models of competence development, the curriculum is not structured by theme-based units, but rather, by learning activities (Mateo, 2006). For this reason, the rubrics are currently used to measure a wide range of higher-order skills or evaluate assignment such as a long-term project, an essay, an exhibit, a lab work, an online course, a demonstration of problem solving, a teamwork or a research report that may vary across discipline (Al-Zumor, 2015;Asari, Ma'rifah, & Arifani 2016;Chujitarom & Piriyasurawong, 2017;Mairing, 2017;Lu & Zhang, 2013). Therefore, scoring rubrics are designed to evaluate the quality of a process -not just the quality of a final-product.…”
Section: Scoring Rubric As Innovative Toolmentioning
confidence: 99%